(untitled) (Medico Legal Update, 2021)
Aim: To investigate the effect of brochure concerning to early postpartum hemorrhage on enhancing nurses’ knowledge, practices and satisfaction. Setting: At obstetric departments in Damanhur teaching hospital at Beheira Governorate. Study Design: A Quasi- experimental (an interventional study) pre and posttest. Sample type: Purposive sample. Sample size: 40 nurse Tools: Three tools 1) A structured interviewing questionnaire. 2) An observational checklist. And 3) Nurses’ satisfaction tool. Results: The result of the present study findings was highly significant improvement in total knowledge and total practical skills among the studied sample pre intervention compared to immediate and eight weeks post intervention. P= < 0.01 Additionally 83% among studied sample satisfied with the advanced knowledge included in the brochure. Conclusion: The present study findings concluded that a significant improvement among studied sample’ knowledge and practices post intervention. Also the majority among the studied sample were satisfied the implemented brochure. Recommendations: Nursing standards, protocols and guideline must be designed to enhance nurses’ knowledge, practices and satisfaction.